Composite solid electrolyte film, preparation method and winding type all-solid-state battery

By filling the composite solid electrolyte film with oxide solid electrolyte in the polymer matrix, the safety hazards and insufficient low-temperature performance of traditional batteries are solved, and a winding all-solid state battery with high energy density and high safety is achieved.

CN119275340APending Publication Date: 2025-01-07DONGGUAN CHAM BATTERY TECH CO LTD

Patent Information

Application Number
CN202411218198.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-02
Publication Date
2025-01-07

AI Technical Summary

Technical Problem

Traditional liquid electrolyte secondary batteries have safety hazards such as liquid leakage and flammability. The application of solid electrolytes in winding batteries is limited by poor mechanical properties and interface contact, insufficient low-temperature performance, making it difficult to meet high energy density and high safety. demand.

Method used

Copolymers of aniline compounds and polyester polymers are used as polymer matrix to fill oxide solid electrolytes, and composite solid electrolyte films are prepared by polymerization and extrusion molding to improve their flexibility and mechanical strength, and to increase low temperatures through hot pressing treatment. Cyclic performance.

Benefits of technology

It realizes high safety performance and good mechanical properties of composite solid electrolyte films, improves the low-temperature cycling and safety performance of winding all-solid state batteries, and is suitable for commercial applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005022178100000091
    Figure BDA0005022178100000091
Patent Text Reader

Abstract

The invention provides a composite solid electrolyte film and a preparation method thereof, and a winding type all-solid-state battery. The composite solid electrolyte film comprises a polymer matrix and an oxide solid electrolyte, the oxide solid electrolyte is filled in the polymer matrix, and the polymer matrix is a copolymer of an aniline compound and a polyester polymer. A copolymer of an aniline compound and a polyester polymer is used as a polymer matrix, so that the prepared composite solid electrolyte film has certain flexibility and can be set to be thin, and a winding type all-solid-state battery can be conveniently assembled subsequently. The oxide solid electrolyte can play a filling role, so that the composite solid electrolyte film has certain mechanical strength besides flexibility; and the conductivity of the composite membrane can be improved, so that the low-temperature cycle performance of the all-solid-state battery is improved. The composite solid electrolyte film adopts an oxide solid electrolyte and a polymer matrix, and no liquid electrolyte exists in the system, so that the safety performance of the battery can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of material preparation, and in particular to a composite solid electrolyte film and a preparation method thereof, and a wound all-solid-state battery. Background Art

[0002] Commercial secondary batteries have been widely used in various fields due to their long cycle life and high energy density. The booming development of energy storage such as portable electronic devices, electric vehicles and power grids has made secondary batteries with higher energy density and better safety an emerging focus. Since traditional secondary batteries usually use liquid electrolytes based on ester solvents such as ethylene carbonate (EC), diethyl carbonate (DEC), and dimethyl carbonate (DMC), there are usually safety hazards such as leakage and flammability, which greatly reduces the safety of secondary batteries.

[0003] Based on this situation, a solid electrolyte that replaces the liquid electrolyte came into being. Solid electrolytes include inorganic solid electrolytes and organic polymer matrices. Compared with liquid electrolytes, solid electrolytes have great safety advantages. However, solid electrolytes currently still have shortcomings that are difficult to overcome. For the current wound batteries, the winding production is difficult and can only be completed in the laboratory. In addition, the mechanical properties and interface contact of inorganic solid electrolytes are poor, and the room temperature ionic conductivity of polymer electrolytes is low, which seriously limits their commercial application process.

[0004] Therefore, there is an urgent need for a new solid electrolyte or a preparation method thereof to meet the needs of lithium-ion batteries with high capacity and high safety performance, while further improving low-temperature performance, etc. Summary of the invention

[0005] The purpose of the present invention is to provide a composite solid electrolyte film and a preparation method thereof, and a wound all-solid-state battery. The composite solid electrolyte film not only has better safety performance, but also has certain mechanical strength and low-temperature performance.

[0006] To achieve the above objectives, the present invention provides a composite solid electrolyte film, comprising a polymer matrix and an oxide solid electrolyte, wherein the oxide solid electrolyte is filled in the polymer matrix, and the polymer matrix is ​​a copolymer of an aniline compound and a polyester polymer.

[0007] In the technical solution adopted by the present invention, a copolymer of an aniline compound and a polyester polymer is used as a polymer matrix. Since it contains amino groups, ester groups, amide groups and the like, the polymer matrix can have a certain flexibility, so the prepared composite solid electrolyte film also has a certain flexibility and the thickness can be set to be relatively thin, so that it can be convenient for subsequent winding to assemble a wound all-solid-state battery. The oxide solid electrolyte filled in the polymer matrix can, on the one hand, act as a filler, so that the composite solid electrolyte film has a certain mechanical strength in addition to flexibility, so as to avoid being damaged during the subsequent assembly into a wound all-solid-state battery; on the other hand, the oxide solid electrolyte can improve the conductivity of the overall composite solid electrolyte film, thereby improving the low-temperature cycle performance of the wound all-solid-state battery. The composite solid electrolyte film of the present invention adopts an oxide solid electrolyte and a polymer matrix, and there is no liquid electrolyte in the system, so the safety performance of the battery can be improved.

[0008] As a technical solution of the present invention, the aniline compound includes at least one of aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine, the polyester polymer includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA), and the oxide solid electrolyte includes at least one of LLZO, LATP, LAGP and LLTO.

[0009] As a technical solution of the present invention, the oxide solid electrolyte accounts for 1 to 10 wt.% of the polymer matrix.

[0010] As a technical solution of the present invention, the composite solid electrolyte film has a thickness of 5 to 12 μm and a flexibility of 1.0 to 5.0 mm.

[0011] A second aspect of the present invention provides a method for preparing a composite solid electrolyte film, comprising the steps of:

[0012] (1) After mixing an aniline compound and a polyester polymer, an initiator and an oxide solid electrolyte are added, and polymerized at 45 to 60° C. for 2 to 12 hours to obtain a gel-like mixture;

[0013] (2) Extruding the mixture at 300-500°C.

[0014] Aniline compounds and polyester polymers are polymerized under the action of an initiator to obtain a gel mixture, which is then extruded to obtain a composite solid electrolyte film with certain flexibility. The film has certain mechanical strength and electrical conductivity.

[0015] As a technical solution of the present invention, the mass ratio of the aniline compound, the polyester polymer and the initiator is 1-5:1-5:0.001-0.010:0.01-0.10.

[0016] As a technical solution of the present invention, the aniline compound includes at least one of aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine, the polyester polymer includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA), the oxide solid electrolyte includes at least one of LLZO, LATP, LAGP and LLTO, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

[0017] The third aspect of the present invention provides the use of the aforementioned composite solid electrolyte film or the composite solid electrolyte film prepared by the aforementioned method for preparing the composite solid electrolyte film in a wound all-solid-state battery.

[0018] The fourth aspect of the present invention provides a method for preparing a wound all-solid-state battery, comprising the steps of laminating and hot-pressing the aforementioned composite solid electrolyte film and pole piece and then winding them. Hot pressing after lamination can reduce the contact impedance between the film and the pole piece, thereby further improving the low-temperature performance of the wound all-solid-state battery.

[0019] As a technical solution of the present invention, the temperature of the hot pressing is 300-500° C., and the pressure is 100-300 MPa. DETAILED DESCRIPTION

[0020] The composite solid electrolyte film of the present invention can be applied to all-solid-state batteries, especially to wound all-solid-state batteries with wound cells. The preparation method of this wound all-solid-state battery may include the steps of laminating the composite solid electrolyte film and the pole piece, hot pressing and then winding. The pole piece can be a conventional all-solid-state battery pole piece, and the positive pole piece can be but not limited to a lithium cobalt oxide pole piece, a lithium manganate pole piece, a lithium iron phosphate pole piece, a nickel cobalt manganate pole piece or a nickel cobalt manganate aluminum pole piece. That is, a pole piece with lithium cobalt oxide, lithium manganate, lithium iron phosphate, nickel cobalt manganate pole piece or nickel cobalt manganate aluminum as the positive electrode active material. Of course, the positive pole piece can also be a pole piece with at least two of lithium cobalt oxide, lithium manganate, lithium iron phosphate, nickel cobalt manganate pole piece and nickel cobalt manganate aluminum mixed as the positive electrode active material. The negative pole piece can be but not limited to a lithium sheet, a carbon negative pole piece or a silicon negative pole piece, that is, a pole piece with metallic lithium, carbon material, or silicon material as the negative electrode active material. The carbon material may be natural graphite, artificial graphite, soft carbon, or hard carbon. The silicon material may be elemental silicon, silicon oxide, or silicon carbon compound. Of course, the negative electrode sheet may also be a sheet in which carbon material and silicon material are mixed as the negative electrode active material. The hot pressing temperature is 300 to 500°C. As an example, the hot pressing temperature may be, but is not limited to, 300°C, 320°C, 340°C, 360°C, 380°C, 400°C, 420°C, 440°C, 460°C, 480°C, and 500°C. The pressure is 100 to 300Mpa. As an example, the pressure may be, but is not limited to, 100Mpa, 120Mpa, 150Mpa, 180Mpa, 200Mpa, 230Mpa, 250Mpa, 280Mpa, and 300Mpa.

[0021] The thickness of the composite solid electrolyte film of the present invention is 5 to 12 μm, and the flexibility is 1.0 to 5.0 mm. The composite solid electrolyte film includes a polymer matrix and an oxide solid electrolyte. The polymer matrix is ​​a copolymer of an aniline compound and a polyester polymer. Among them, the aniline compound includes at least one of aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine. The polyester polymer includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA). The mass ratio of the aniline compound to the polyester polymer is 1 to 5:1 to 5, as an example, it can be but not limited to 1:1, 1:2, 1:3, 1:4, 1:5, 3:1, 3:2, 2:3, 3:4, 3:5, 4:5, 5:1, 5:2, 5:3, 5:4. The oxide solid electrolyte is filled in the polymer matrix, and the oxide solid electrolyte includes at least one of LLZO, LATP, LAGP and LLTO. The oxide solid electrolyte accounts for 1 to 10 wt.% of the polymer matrix. As an example, the proportion of the oxide solid electrolyte can be but is not limited to 1 wt.%, 2 wt.%, 3 wt.%, 4 wt.%, 5 wt.%, 6 wt.%, 7 wt.%, 8 wt.%, 9 wt.%, and 10 wt.%.

[0022] The preparation method of the composite solid electrolyte film of the present invention comprises the following steps: (1) mixing an aniline compound and a polyester polymer, adding an initiator and an oxide solid electrolyte, and polymerizing at 45 to 60° C. for 2 to 12 hours to obtain a gel-like mixture; and (2) extruding the mixture at 300 to 500° C. to form the mixture.

[0023] Wherein, the mass ratio of the aniline compound, the polyester polymer and the initiator is 1-5:1-5:0.001-0.010:0.01-0.10, for example, but not limited to 1:1:0.001:0.01, 3:1:0.001:0.05, 5:1:0.001:0.10, 1:1:0.004:0.01, 1:3:0.004:0.05, 1:5: 0.004:0.10, 1:1:0.010:0.01, 1:3:0.010:0.05, 1:5:0.010:0.10, 1:3:0.001:0.01, 3:3:0.001:0.05, 5:3:0.001:0.10, 1:5:0.001:0.01, 3:5:0.001:0.05, 5:5:0.001:0.10. The aniline compound includes at least one of aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine. The polyester polymer includes polyethylene glycol diacrylate (PEGDA) and / or polypropylene glycol diacrylate (PPGDA). The oxide solid electrolyte includes at least one of LLZO, LATP, LAGP and LLTO. The initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

[0024] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.

[0025] Example 1

[0026] This embodiment is a composite solid electrolyte film. The composite solid electrolyte film includes a polymer matrix and LATP. The polymer matrix is ​​a copolymer of aniline, o-phenylenediamine and polyethylene glycol diacrylate.

[0027] The preparation method of the composite solid electrolyte film comprises the following steps:

[0028] (1) Aniline, o-phenylenediamine and polyethylene glycol diacrylate are mixed in a mass ratio of 1:3:2 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, 5 wt.% of LATP is added to the first mixture and mixed evenly, and polymerized at 50° C. for 8 h to obtain a second mixture in a gel state;

[0029] (2) Extruding the second mixture at 450° C. and a pressure of 200 MPa to obtain a composite solid electrolyte film.

[0030] Example 2

[0031] This embodiment is a composite solid electrolyte film. The composite solid electrolyte film includes a polymer matrix and LLZO. The polymer matrix is ​​a copolymer of aniline, p-phenylenediamine and polyethylene glycol diacrylate.

[0032] The preparation method of the composite solid electrolyte film comprises the following steps:

[0033] (1) Aniline, p-phenylenediamine and polyethylene glycol diacrylate are mixed in a mass ratio of 1:3:2 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, 5 wt.% of LLZO is added to the first mixture and mixed evenly, and polymerized at 50° C. for 8 h to obtain a second mixture in a gel state;

[0034] (2) Extruding the second mixture at 450° C. and a pressure of 200 MPa to obtain a composite solid electrolyte film.

[0035] Example 3

[0036] This embodiment is a composite solid electrolyte film. The composite solid electrolyte film includes a polymer matrix and LAGP. The polymer matrix is ​​a copolymer of o-phenylenediamine and polypropylene glycol diacrylate.

[0037] The preparation method of the composite solid electrolyte film comprises the following steps:

[0038] (1) o-phenylenediamine and polypropylene glycol diacrylate are mixed in a mass ratio of 3:2 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, 5 wt.% of LAGP is added to the first mixture and mixed evenly, and polymerized at 50° C. for 8 h to obtain a second mixture in a gel state;

[0039] (2) Extruding the second mixture at 450° C. and a pressure of 200 MPa to obtain a composite solid electrolyte film.

[0040] Example 4

[0041] This embodiment is a composite solid electrolyte film. The composite solid electrolyte film includes a polymer matrix and LATP. The polymer matrix is ​​a copolymer of aniline, o-phenylenediamine and polyethylene glycol diacrylate.

[0042] The preparation method of the composite solid electrolyte film comprises the following steps:

[0043] (1) Aniline, o-phenylenediamine and polyethylene glycol diacrylate are mixed in a mass ratio of 1:4:3 to obtain a first mixture, 0.6 wt.% of azobisisoheptanenitrile is added to the first mixture and mixed evenly, then 8 wt.% of LATP is added to the first mixture and mixed evenly, and polymerized at 55° C. for 10 h to obtain a second mixture in a gel state;

[0044] (2) Extruding the second mixture at 400° C. and a pressure of 280 MPa to obtain a composite solid electrolyte film.

[0045] Comparative Example 1

[0046] This comparative example is a composite solid electrolyte film, which includes a polymer matrix and graphene, wherein the polymer matrix is ​​a copolymer of aniline, o-phenylenediamine and polyethylene glycol diacrylate.

[0047] The preparation method of the composite solid electrolyte film comprises the following steps:

[0048] (1) Aniline, o-phenylenediamine and polyethylene glycol diacrylate are mixed in a mass ratio of 1:3:2 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, 5 wt.% of graphene is added to the first mixture and mixed evenly, and polymerized at 50° C. for 8 h to obtain a second mixture in a gel state;

[0049] (2) Extruding the second mixture at 450° C. and a pressure of 200 MPa to obtain a composite solid electrolyte film.

[0050] Comparative Example 2

[0051] This comparative example is a composite solid electrolyte film. The composite solid electrolyte film includes a polymer matrix and LATP. The polymer matrix is ​​a copolymer of vinylene carbonate, o-phenylenediamine and polyethylene glycol diacrylate. The preparation method of the composite solid electrolyte film includes the steps of:

[0052] (1) vinylene carbonate, o-phenylenediamine and polyethylene glycol diacrylate are mixed in a mass ratio of 1:3:2 to obtain a first mixture, 0.5 wt.% of azobisisobutyronitrile is added to the first mixture and mixed evenly, 5 wt.% of LATP is added to the first mixture and mixed evenly, and polymerized at 50° C. for 8 h to obtain a second mixture in a gel state;

[0053] (2) Extruding the second mixture at 450° C. and a pressure of 200 MPa to obtain a composite solid electrolyte film.

[0054] The thickness, flexibility and rigidity of the composite solid electrolyte films prepared in Examples 1 to 4 and Comparative Examples 1 to 2 were tested. The thickness was tested using a thickness gauge. The flexibility and rigidity were tested as follows. The test results are shown in Table 1.

[0055] Flexibility test: Use shafts of different diameters, with curvature radii of 0.5mm, 1.0mm, 1.5mm, 2.0mm, 2.5mm, 5.0mm and 7.5mm. During the test, place the film to be tested on shafts of different diameters and test the flexibility of the coating by bending. The shaft with the smallest diameter shows no cracks in the film under optical microscope observation, and the number of millimeters of its diameter is the evaluation value of flexibility.

[0056] Rigidity test: Use a cutter to punch out samples of 90×15mm and 60.5×15mm in size from the film to be tested in the longitudinal direction (MD) and transverse direction (TD), respectively. Place the samples in the fixtures at both ends of the tensile testing machine for testing. The tensile speed is 50mm / min. Measure multiple times (N≥3) and take the maximum value.

[0057] Table 1 Thickness, flexibility and rigidity of the composite solid electrolyte films obtained in Examples 1 to 4 and Comparative Examples 1 to 2

[0058] Test items Thickness(μm) Flexibility(mm) <![CDATA[Rigidity (N / m 2 )]]> Example 1 5 1.0 1360 Example 2 5 1.0 1383 Example 3 5 1.0 1346 Example 4 5 1.0 1373 Comparative Example 1 5 15.0 2566 Comparative Example 2 5 10.0 2312

[0059] From the results in Table 1, it can be seen that the composite solid electrolyte film prepared by using the copolymer of aniline compounds and polyester polymers as the polymer matrix and the filled oxide solid electrolyte is relatively thin and has certain flexibility and rigidity. If graphene is used to replace the oxide solid electrolyte, the rigidity will be too large, which is not conducive to the assembly of a wound all-solid-state battery. Adding vinylene carbonate on the basis of using aniline compounds and polyester polymers as polymerization monomers will greatly reduce the flexibility of the generated polymer, which is also not conducive to the subsequent assembly of a wound all-solid-state battery.

[0060] The composite solid electrolyte films and the positive and negative electrodes of Examples 1 to 3 were assembled into a wound all-solid-state battery, and the preparation process was as follows. The electrochemical performance of the prepared all-solid-state battery was tested under the following test conditions, and the test results are shown in Table 2.

[0061] (I) Preparation of wound all-solid-state batteries

[0062] (1) Lithium cobalt oxide, PVDF and acetylene black were mixed with solvent NMP at a mass ratio of 90:5:5 to obtain a positive electrode slurry. The positive electrode slurry was evenly coated on an aluminum foil, and then dried in a vacuum oven at 120° C. for 12 hours to form a positive electrode sheet.

[0063] (2) Artificial graphite, CMC, SBR and acetylene black were mixed with deionized water as a solvent at a mass ratio of 92:2:3:3 to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on a copper foil, and then dried in a vacuum oven at 120° C. for 12 hours to form a negative electrode sheet.

[0064] The positive electrode sheet, solid electrolyte film and negative electrode sheet are stacked, and then hot-pressed and rolled at 450°C to obtain a rolled all-solid-state battery.

[0065] (II) Electrochemical performance test

[0066] (1) Normal temperature cycle performance test

[0067] The wound all-solid-state battery was placed in an environment of 25°C, charged at a constant current of 1C to 4.2V, then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1C to 2.5V. This cycle was repeated for 500 times, and the discharge capacity of the first cycle and the last cycle were recorded. The capacity retention rate of the normal temperature cycle was calculated according to the following formula.

[0068] Capacity retention rate = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%

[0069] (2) High temperature cycle performance test

[0070] The wound all-solid-state battery was placed in an environment of 45°C, charged at a constant current of 1C to 4.2V, then charged at a constant voltage to a current of 0.05C, and then discharged at a constant current of 1C to 2.5V. This cycle was repeated for 500 times, and the discharge capacity of the first cycle and the last cycle were recorded. The capacity retention rate of the high-temperature cycle was calculated according to the following formula.

[0071] Capacity retention rate = discharge capacity of the last cycle / discharge capacity of the first cycle × 100%

[0072] (3) Low temperature performance test

[0073] The wound all-solid-state battery was placed in an environment of 25°C and charged and discharged at 0.5C / 0.5 (battery cut-off voltage was 3.0V, discharge capacity was C0), and the upper limit voltage was 4.2V (cut-off current was 0.05C). Then the battery was fully charged to 4.2V (cut-off current was 0.05C) at 0.5C at 25°C, and then transferred to -20°C for 4h, and discharged to 3.0V at 0.5C, with a discharge capacity of C1, and the capacity retention rate was calculated.

[0074] Capacity retention rate = (C1 / C0)*100%

[0075] Table 2 Electrochemical performance test results of Examples 1 to 3

[0076]

[0077] From the results in Table 1, it can be seen that the composite solid electrolyte film prepared by using a copolymer of aniline compounds and polyester polymers as a polymer matrix and then filling an oxide solid electrolyte is used to prepare a wound all-solid-state battery, which has better cycle and low-temperature performance, especially at a high temperature of 45°C. This is because the filled oxide solid electrolyte can improve the conductivity of the overall composite solid electrolyte film, thereby improving the low-temperature cycle performance of the wound all-solid-state battery. Moreover, the composite solid electrolyte film uses an oxide solid electrolyte and a polymer matrix, and there is no liquid electrolyte in the system, so the safety performance of the battery at high temperature can be improved.

[0078] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A composite solid electrolyte film, characterized in that: The invention comprises a polymer matrix and an oxide solid electrolyte, wherein the oxide solid electrolyte is filled in the polymer matrix, and the polymer matrix is ​​a copolymer of an aniline compound and a polyester polymer.

2. The composite solid electrolyte film according to claim 1, characterized in that: The aniline compound includes at least one of aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine, the polyester polymer includes polyethylene glycol diacrylate and / or polypropylene glycol diacrylate, and the oxide solid electrolyte includes at least one of LLZO, LATP, LAGP and LLTO.

3. The composite solid electrolyte film according to claim 1, characterized in that: The oxide solid electrolyte accounts for 1 to 10 wt.% of the polymer matrix.

4. The composite solid electrolyte film according to claim 1, characterized in that: The composite solid electrolyte film has a thickness of 5 to 12 μm and a flexibility of 1.0 to 5.0 mm.

5. A method for preparing a composite solid electrolyte film, characterized in that: Includes steps: (1) After mixing an aniline compound and a polyester polymer, an initiator and an oxide solid electrolyte are added, and polymerized at 45 to 60° C. for 2 to 12 hours to obtain a gel-like mixture; (2) Extruding the mixture at 300-500°C.

6. The method for preparing a composite solid electrolyte film according to claim 5, characterized in that: The mass ratio of the aniline compound, the polyester polymer and the initiator is 1-5:1-5:0.001-0.010:0.01-0.

10.

7. The method for preparing a composite solid electrolyte film according to claim 5, characterized in that: The aniline compound includes at least one of aniline, o-phenylenediamine, m-phenylenediamine and p-phenylenediamine, the polyester polymer includes polyethylene glycol diacrylate / or polypropylene glycol diacrylate, the oxide solid electrolyte includes at least one of LLZO, LATP, LAGP and LLTO, and the initiator includes at least one of azobisisobutyronitrile, azobisisoheptanenitrile and dimethyl azobisisobutyrate.

8. Use of the composite solid electrolyte film prepared by the composite solid electrolyte film according to any one of claims 1 to 4 or the method for preparing a composite solid electrolyte film according to any one of claims 5 to 7 in a wound all-solid-state battery.

9. A method for preparing a wound all-solid-state battery, characterized in that: The method comprises the steps of laminating and hot-pressing the composite solid electrolyte film according to any one of claims 1 to 4 or the composite solid electrolyte film prepared by the method for preparing the composite solid electrolyte film according to any one of claims 5 to 7 and the electrode sheet, and then winding the laminate.

10. The method for preparing a wound all-solid-state battery according to claim 9, characterized in that: The temperature of the hot pressing is 300-500° C., and the pressure is 100-300 MPa.

Citation Information

Patent Citations

  • Battery cell with anode protective layer

    CN110710024A

  • In-situ polymerization solid polymer electrolyte and preparation method thereof

    CN115882059A

Cited By

  • Polyformaldehyde halide composite solid electrolyte and preparation method thereof

    CN122267271A